Biodiversity of suprabenthic peracarid assemblages from the Blanes Canyon region (NW Mediterranean Sea) in relation to natural disturbance and trawling pressure. (March 2017) - Almeida, Mariana; Frutos, Inmaculada; Company, Joan B.; Martin, Daniel; Romano, Chiara; Cunha, Marina R.
Abstract: Blanes Canyon and its adjacent margin are important fishery areas (mainly by bottom trawling) located in a highly energetic oceanographic setting in the NW Mediterranean Sea. Here we assess the spatial and temporal variability in abundance, diversity and community structure of the suprabenthic peracarid assemblages in this region and examine this variability in relation to the natural and anthropogenic (trawling fisheries) disturbance regimes. The sampling was conducted between March 2003 and May 2004 in three main fishing grounds, the canyon head (average depth: 490 m), the canyon wall (average depth: 550 m) and the eastern adjacent slope (average depth: 820 m), as well as in two non-exploited areas in the western (at 900 m depth) and eastern (at 1500 m depth) slope near the canyon mouth. A total of 138 species were identified, with amphipods being the most speciose and abundant group, followed by mysids in terms of abundance. Our results show high spatial and temporal variability in suprabenthic assemblages. Densities were higher in the canyon head and western slope, which appear to be the preferential routes for water masses and particle fluxes in months of flood events, and other energetic processes. In the canyon head, where periodic erosion processes are more active, low diversity, high dominance and higher turnover (β-diversity) were observed, apparently coupled with significant temporal fluctuations in the densities of the highly motile component of suprabenthos (mysids, predatory and scavenging amphipods). In the sedimentary more stable eastern slope, high diversity values were observed, accompanied by a higher relative contribution of the less motile groups (i.e. amphipods, most isopods, cumaceans). These groups have a closer interaction with the sediment where they exploit different food sources and are more susceptible to physical disturbance. Temporal variability in their diversity may be related to changes in food quality rather than quantity. In the canyon wall, temporal fluctuations in diversity indices were only revealed in relation to the overall higher and more continued fishing pressure observed in the canyon wall fishing ground (Cara Norte/Sot site). Here, species richness and abundance declined with increasing fishing pressure but the lowest trophic and taxonomic diversities were observed under intermediate levels of disturbance. These findings underline (i) the differences between relatively low and highly motile taxa in terms of response to disturbance events; (ii) the differences between assemblages subjected to different levels of natural disturbance and trawling pressure, which modify the common bathymetric patterns of abundance and diversity often described from continental margins.